2008
DOI: 10.1038/nm1780
|View full text |Cite
|
Sign up to set email alerts
|

Aggravation of viral hepatitis by platelet-derived serotonin

Abstract: More than 500 million people worldwide are persistently infected with hepatitis B virus or hepatitis C virus 1 . Although both viruses are poorly cytopathic, persistence of either virus carries a risk of chronic liver inflammation, potentially resulting in liver steatosis, liver cirrhosis, end-stage liver failure or hepatocellular carcinoma. Virus-specific T cells are a major determinant of the outcome of hepatitis, as they contribute to the early control of chronic hepatitis viruses, but they also mediate imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
198
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 217 publications
(204 citation statements)
references
References 26 publications
6
198
0
Order By: Relevance
“…Lang et al 4 found that treatment with 5-HT in infected mice aggravated liver damage by delaying virus clearance. In contrast, mice lacking serotonin accelerated virus clearance and reduced liver damage.…”
mentioning
confidence: 99%
“…Lang et al 4 found that treatment with 5-HT in infected mice aggravated liver damage by delaying virus clearance. In contrast, mice lacking serotonin accelerated virus clearance and reduced liver damage.…”
mentioning
confidence: 99%
“…However, in patients affected by ALD the scenario is opposite, with chronic consumption ethanol reported to suppress activation of NKT cells, then facilitating fibrogenesis and then fibrosis. In a recent exhaustive review Gao and Radaeva [128] Serotonin, as a molecule involved in normal wound healing, can either stimulate vasoconstriction or vasodilation depending on the specific tissue in which is released (in the liver, 5-HT is believed to promote vasoconstriction of liver sinusoids) depending likely to the specific 5-HT receptors which are expressed on vascular endothelial and smooth muscle cells [142]. More relevant, serotonin contributes apparently to leukocyte recruitment and retention at the site of injury and has been reported to affect behavior and function of cells of innate and adaptive immunity.…”
Section: Natural Killer and Natural Killer T Cells In Liver Fibrogenementioning
confidence: 99%
“…[4][5][6][7][8] Macrophages are resident in every organ of the body. [9][10][11] With their potent phagocytic capacity, they act as a first line of defense between pathogens entering tissues through the bloodstream and parenchymal cells.…”
mentioning
confidence: 99%